Availability and readiness of primary healthcare facilities for the management of non-communicable diseases in different districts of Punjab, Pakistan - Rashid, Sadaf; Mahmood, Humaira; Asma Iftikhar, Asma; komal, Nimrah; Butt, Zikria; Mumtaz, Hassan; Shellah, Duha (Frontiers in Public Health, 2023)
Introduction: Non-communicable diseases (NCDs) and their effects are rising quickly. Non-communicable diseases (NCDs) such cardiovascular illnesses, diabetes, cancer, and chronic lung diseases cause 60% of global deaths, 80% of which occur in developing countries. In established health systems, primary care handles most NCD care. Methodology: This mixed method study is conducted to analyze the health service availability and readiness towards the non-communicable diseases using the SARA tool. It includes 25 Basic Health Unites (BHUs) from different districts of Punjab. Quantitative data was collected using the SARA tools while, the qualitative data was collected through in-depth interviews with healthcare providers working at the BHUs. Results: Fifty- two percent of the BHUs face the problem of load shedding of both electricity and water that leads to the poor availability of the health care services. Eight (32%) out of 25 BHU’s provide the diagnosis or management of non-communicable diseases. The service availability was highest for the diabetes mellitus (72%), followed by cardiovascular disease (52%), then chronic respiratory disease (40%). No services were available for cancer at the BHU level. Conclusion: This study raises issues and questions about the primary healthcare system in the Punjab in two areas: first, the overall performance system, and second, the readiness of basic healthcare institutions to treat noncommunicable diseases (NCDs). The data show that there are many persisting PHC deficiencies. The study found a major training and resource deficit (guidelines, promotional materials). Therefore, it's important to include NCD prevention and control training in district training activities. Noncommunicable diseases (NCDs) are underrecognized in primary health care (PHC).